The practices of modern criminal defence lawyers: Alienation and its implications for access to justice. (March 2019) - Newman, Daniel; Welsh, Lucy
This article marries two sets of independently gathered empirical data (observation and interviews) to argue that English criminal defence lawyers currently present as alienated workers. We seek to revive and revisit theories of alienation that are grounded in Marxism and use them as a lens through which lawyers' behaviour can be viewed and understood. Building on a Marxist application of alienation, we offer a refined analysis premised upon a contemporary understanding of how alienation plays out in criminal defence work during the neoliberal era. We highlight that the way lawyers talk about their roles suggests that they have lost a sense of purpose, and feel powerless and undervalued. We argue that those feelings appear to have developed as a result of structural change—most notably funding cuts and demands for efficiency—which seem to be grounded in what can broadly be understood as neoliberal political ideology and austerity measures. We further suggest that such structural change and resultant feelings of alienation have implications for the quality of service that defendants receive.